Emulation of Radius-to-Fix legs in Departure Routes via Fly-By Turns - Carlos GONZAGA-LOPEZ; Florian Michael BUCHMANN; Henrik EKSTRAND; Andreas LINNÉR; Philipp Daniel SCHAAD (INCAS Bulletin, 2019)
The results of a preliminary study on the emulation of radius-to-fix legs in turning departures by means of standard track-to-fix legs are presented in this technical note. While radius-to-fix equipage rates keep gradually increasing over time, a traffic mix containing aircraft with and without this navigation capability can impede an optimal management of the traffic flows whenever precise and repeatable curved flight paths are required. After test-flying various sequences of track-to-fix segments to emulate a reference constant-radius arc in a typical departure environment, the deviations to the desired flight path and the flyability aspects were assessed. The first results for a given scenario and aircraft type show an adequate path conformance for a navigation specification RNAV/RNP 1 within a certain range of aircraft performances and weather conditions. However, the reduced predictability of the roll steering when transitioning between track-to-fix segments and the high frequency in the oscillations of the bank angle may pose a problem to flight crews and passengers, respectively.